Male Courtship Pheromones Induce Cloacal Gaping in Female Newts (Salamandridae) - Janssenswillen, Sunita (PLoS One, 2016)
Pheromones are an important component of sexual communication in courting salamanders, but the number of species in which their use has been demonstrated with behavioral evidence remains limited. Here we developed a behavioral assay for demonstrating courtship pheromone use in the aquatically courting Iberian ribbed newt Pleurodeles waltl. By performing an in-depth study of the courtship behavior, we show that females invariably open their cloaca (cloacal gaping) before engaging in pinwheel behavior, the circling movement that is the prelude to spermatophore uptake. In contrast, cloacal gaping was not observed in failed courtships, where females escaped or displayed thanatosis. Since gaping mainly occurred during male amplexus and cloacal imposition, which is the obvious period of pheromone transfer, we next investigated whether male courtship water (i.e., water holding courtship pheromones) alone was able to induce this reaction in females. These tests showed that courtship water induced cloacal gaping significantly more than water, even in the absence of a male. Cloacal gaping thus provides a simple and robust test for demonstrating courtship pheromone use in the Iberian ribbed newt. Since opening the cloaca is an essential prerequisite for spermatophore pick-up in all internally fertilizing salamanders, we hypothesize that variations on this assay will also be useful in several other species.